Dental And Oral Health Counseling Efforts On Students' Knowledge Levels (SDN 02 Tiron Madiun) - Wardani, Novelia Eka Pri; Putri, Annisa Wiratna; Ramadhanintyas, Karina Nur (Health Science UDINUS, 2023)
Dental and oral health is an integral part of body health. To achieve optimal dental and oral health, periodic treatment must be carried out. At SDN 02 Tiron Madiun, there has never been any socialization about oral and dental health. The purpose of this study is to analyze dental and oral health extension efforts on students' level of knowledge. The research method used is quasi-experimental with a research design of one group pretest posttest design. The study was conducted at SDN 02 Tiron Madiun with 22 respondents. The Wilcoxon signed rank test is used to analyze the data. Based on the data obtained, it shows that 22 respondents have a level of knowledge with a good category, 21 people (95.5%) and this study shows the influence of dental and oral health counseling on students' knowledge level (p = 0.021). Intervention in the form of counseling with poster media can significantly increase student knowledge. Provision of knowledge and teaching about dental and oral health from an early age to reduce the incidence of dental caries in school-age children.